ANALYSIS OF ROLLING FRICTION BETWEEN TRIANGULAR TOOTH TYPE FRICTION WHEEL AND FLEXIBLE TRACK UNDER SMALL DEFORMATION CONTACT - ZHANG ZhiChen; ZHAO XueMin; TANG DeYu; LIU MingZhu; LI LiangYu; LONG Bin (Jixie qiangdu)
In this paper,we study the rolling friction of the triangular tooth friction wheel and the flexible track under the condition of small deformation contact. According to the Crook ’s elastic plastic rolling friction theory,the flexible rail is established by the finite element model,and the rolling friction coefficient and rolling friction are analyzed. Rolling friction force measurement is designed to measure the rolling friction torque,the theoretical value and the calculated value are compared,and the suitable rolling friction model is obtained.